(untitled) (Research, Society and Development, 2021)
The plasma membrane is a structure of great importance present in all living beings, performing other functions in addition to the transport of substances. This article has as main objective to propose a practical class to facilitate the process of teaching and learning the cell membrane to high school students, in the discipline of Biology. Using simple and low-cost materials such as beets (Beta vulgaris, L.), water, kerosene and alcohol, this class allows the teacher to work with students on the concepts of membrane permeability, in addition to other related subjects. Thus, the proposed practical class can be reproduced not only in the school environment, but also at home by the students. We believe that the approach of the proposed practical class can allow the application of the concepts experienced in the theoretical classes, facilitating the learning of the proposed theme, in addition to promoting the discussion and proposition of hypotheses, awakening the perspective of scientific experimentation of the students.